Reimagining Class in Australia : Marxism, Populism and Social Science - Paternoster, Henry (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book re-evaluates New Left and Marxist texts from the 1980s, in order to explore problems facing the study of 'class' which have emerged within Australian and international theories. The author contrasts the popular ideas of Connell, Bourdieu and the 'Death of Class' thesis, with those of lesser known texts, concluding that no single definition can account for the various historical meanings of class. Instead, loosely following Castoriadis, the concept of class can best be understood as creatively imagined and institutionalised. Paternoster proposes that class is best studied through historical phenomenology, which can be used to link political economy, cultural sociology and anthropological ethnographies. This approach allows the contributions of Marxist and New Left authors to be reintegrated with contemporary theories. Doing so highlights the significance of labour populism, while cautioning against the ahistorical applications of texts such as Boudieu's Distinction. Reimagining Class in Australia will be of interest to students and scholars across a range of disciplines, including sociology, history, political economy and anthropology.
Keywords: Social sciences.; Political theory.; Social structure.; Social inequality.; Social sciences -- Philosophy.; elektronické knihy; electronic books